Maz Resources Sdn Bhd / Siti Nuur Rafidah Ismail - Ismail, Siti Nuur Rafidah (Universiti Teknologi MARA, Sarawak, 2016)
MAZ Resources Sdn. Bhd (640468) is a Sirim Berhad incubator which is wholly owned by Bumiputra. It was incorporated in Malaysia on January 21s' 2004 with a paid up capital of RM500,000.00. MAZ Resources Sdn Bhd is led by the Board of Director namely Wan Muslim Wan Mustafa and Wan Musliha Wan Mustafa and the share holders of the company is Wan Muslim Wan Mustafa, Wan Musliha Wan Mustafa, and Zulkifli Idris. MAZ Resources Sdn Bhd is a local entrepreneur that maximizes the talents of experienced and professional local practitioner under the supervision by Sirim Berhad who work together purposely to fulfil the need for Malaysia to develop its own capabilities in the cleaning industries for various sectors. MAZ Resources Sdn Bhd is fully operated at their registered address at SIRIM BERHAD Cawangan Terengganu, Lot PT 1929P, Kawasan Perindustrian Chendering, 21080 Kuala Terengganu, Terengganu Darul Iman.